1993
DOI: 10.1002/pd.1970130807
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 2928 CVS samples and 1075 amniocenteses from randomized studies

Abstract: We report cytogenetic results from a randomized Danish chorionic villus sampling (CVS) and amniocentesis (AC) study including 2928 placental and 1075 amniotic fluid specimens processed in the same laboratory. The results are presented in groups comparing CVS with amniocentesis and transabdominal (TA) CVS with transcervical (TC) CVS as randomized. More abnormalities and more ambiguous diagnostic problems were found in placental tissues than in amniotic cells. There were no diagnostic errors and no incorrect sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
0
23
1
1
Order By: Relevance
“…Nevertheless, follow-up amniocentesis should be recommended in level III mosaic findings in CVS, irrespective of their percentage in the analysis. In our sample, MCC was found to be much lower (0.5%) than reported in other studies, 3,[20][21][22] and the low rate of MCC was independent of the procedure, TA vs. TC. We believe that the laboratory procedure for cleaning the villi is an important factor in low MCC rather than the type of sampling technique, as is suggested in other reports.…”
Section: Discussioncontrasting
confidence: 53%
“…Nevertheless, follow-up amniocentesis should be recommended in level III mosaic findings in CVS, irrespective of their percentage in the analysis. In our sample, MCC was found to be much lower (0.5%) than reported in other studies, 3,[20][21][22] and the low rate of MCC was independent of the procedure, TA vs. TC. We believe that the laboratory procedure for cleaning the villi is an important factor in low MCC rather than the type of sampling technique, as is suggested in other reports.…”
Section: Discussioncontrasting
confidence: 53%
“…Lack of chromosome analysis after spontaneous and induced abortion results in (a) unclassifiable cases which make interpretation of compiled data less clear and (b) a potential underestimation of the number of false-negative diagnoses if normal CVS results are not followed up by chromosomal analysis of the fetus and (c) a potential underestimation of the number of falsepositive diagnoses if abnormal CVS results are not followed by chromosome analysis of the aborted fetus. However, it has been shown on earlier CVS studies that the vast majority of non-mosaic abnormalities diagnosed on CVS can be confirmed in the aborted fetus (Mikkelsen and Aymé, 1987;Ledbetter et al, 1992;Smidt-Jensen et al, 1993). In our study, the 2321 non-ambiguous, nonmosaic chromosome abnormalities found in the 62 865 CV samples (3·7 per cent) included abnormalities that were either confirmed in the aborted fetus or apparently present, based on clinical evidence.…”
Section: Problems In the Classification Of Resultsmentioning
confidence: 68%
“…In the UK study (Association of Clinical Cytogeneticists Working Party on Chorionic Villi in Prenatal Diagnosis, 1994) 0.5% MCC and in the US study (Ledbetter et al, 1992) 2.16% MCC at transcervical sampling was found. Only Smidt-Jensen et al (1993) found a higher percentage of MCC, namely 4.2%. The reason for the high percentage in the present study could be that all male karyotypes were carefully screened for XX cells.…”
Section: Discussionmentioning
confidence: 99%